“Terres de Rivières” - Cazzola, Alessandra (Ri-Vista. Research for landscape architecture, 2015)
Terre de Rivières is the outcome of a collaborative research undertaken with a EU funded project by the same name, which culminated in an international seminar held in November 2006. The workshop presents a collection of case studies on rivers and river regions each taking into account diverse aspects, including geographical, administrative and institutional variables. The case studies have been organized into three sections: Planning, Ecology and Education-Communication. This doesn’t imply, a gap between these fields, which are all - inevitably - cross-cutting in nature.